Public Private Partnership in the European Union: Experiences in the UK, Germany and Austria - Ronald W. McQuaid; Walter Scherrer (Central European Public Administration Review)
The political context of governments differs between the UK, Germany and Austria, but each government currently has a positive view of Public private Partnership (PPP). There are many similarities to the drivers for PPPs in Austria, Germany and the UK. The UK has had more experience, and the conservative-led government in Austria has been moving towards greater use of PPPs of the “privatisation”-type, but only very cautiously towards PPPs of the “PFI-type”. The major motives for moving towards PPPs are macroeconomic or budgetary, especially in Germany and Austria, but also microeconomic or improving the efficiency of public service delivery, especially in the UK. In all three countries PPPs appear to be a systematic middle response to the alternatives of privatisation or public service provision of infrastructure and operational support. There are more significant multi-tiered levels of government in the Federal systems of Germany and Austria, with many autonomous players including federal government, states and municipalities. Investment by the latter two exceeds investment expenditure of the federal government. In the more centralised UK system policies towards PPPs have been relatively rapid and similar, although not identical, across the UK. In Germany the search for a comprehensive approach (Gesamtkonzept) has slowed the dissemination of PPP; Austria seems to handle the issue more pragmatically. One issue that remains crucial to the future impacts of PPPs is whether they offer genuine and sustainable increases in efficiency and effectiveness compared to the alternatives. If they do then they should have a positive impact on future public resource availability, but if they do not then they may provide short-term financial and political benefits, but at the cost of constraining future decision makers and placing greater pressures on public finances in the longer-term.